The Russian Public Consciousness Metamorphoses in Conditions of Technogenic Sociocultural Reality - Kryuchkova, Svetlana E.; Khrapov, Sergey A.; Mironova, Yulia G.; Tyrnova, Natalia A.; Leonova, Olga V. (Journal of History Culture and Art Research, 2017)
A problem of complex philosophic analysis of the Russian public consciousness transformation in conditions of technogenic sociocultural reality (processes of technological development, informatization, and virtualization, axiologisation of the technogenic and deaxiologisation of the humanistic) is the objective of the research. Special attention is paid to determining technogenic metamorphoses and structural and functional trends of public consciousness dynamics in Russia. Content and structural and functional technogenic public consciousness metamorphoses are reflected by conjugating philosophical methodology of research with the categorical apparatus and methods of social psychology, cultural-historical psychology and social cognitive science. The scientific novelty of research consists in revealing main technogenic Russian public consciousness metamorphoses as well as in determining the following structural and functional trends; a) an additional intermediate mechanism between a human and public consciousness has emerged; b) opportunity to obtain a ready-made cognitive product promote reducing cognitive and social human activity as well as rupture of the individual and public consciousness; c) information field grows, as well as its fragmentation, depending on the possibilities of access and individual preferences; d) information values of "novelty" and "speed" have changed not only the type of human existence, but the mechanisms of public consciousness functioning as well; e) for modern man escapism into zones of the virtual and of the irrational becomes more and more important, and this changes the ontological attributes of public consciousness.